Clinical observation and anti-drug antibody monitoring of enzyme replacement therapy in children with Fabry disease - Lu, Z H (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2025)
Objective: To analyze the efficacy of enzyme replacement therapy and anti-drug antibody production in children with Fabry disease. Methods: The clinical data of 7 children with Fabry disease treated with enzyme replacement therapy for more than 1 year at Children's Hospital of Zhejiang University School of Medicine from July 2021 to June 2024 were retrospectively analyzed. The basic information and the changes of related clinical indicators before and after treatment were collected. Paired sample t test was used to compare renal function, left heart mass index, pain score and other related indexes before and after treatment. The anti-drug antibodies were detected by enzyme-linked immunosorbent assay. Results: A total of 6 boys and 1 girl were included. The age of diagnosis was (12.2±1.8) years. After 1 year of enzyme replacement therapy, the abnormal substrate globotriaosylsphingosine and brief pain inventory scores of all children were significantly lower than those before treatment ((16±11) vs. (63±42) μg/L, (22±19) vs. (45±29) points, t=3.88, 3.43, both P<0.05). There were no significant differences in glomerular filtration rate, urinary microalbumin to creatinine and left heart mass index before and after treatment ((124±35) vs. (136±26) ml/(min·1.73 m2), (9.3±8.3) vs. (3.8±2.5) mg/g, (38±9) vs. (33±6) g/m2.7, t=1.33, 1.74, 1.19, all P>0.05). Patients 4, 5 and 6 developed anti-drug antibodies at 1 month, 4 months and 1 month after medication, respectively. Patient 4 had persistently high anti-drug antibody titers (absorbance 3.65-3.73) accompanied by urticaria, elevated globotriaosylsphingosine and worsening clinical symptoms. Conclusions: The enzyme replacement therapy can effectively improve the clinical symptoms and reduce the level of globotriaosylsphingosine in children with Fabry disease. The anti-drug antibody is common in patients after long-term enzyme replacement therapy and may diminish the efficacy, which needs dynamic monitoring